Subsurface geology and structural trend evaluation of dam using multi-techniques - Oluwaseun Victoria Fatoye; Samuel Abiodun Adebayo; Johnson Kayode Ayeni; Jeremiah Olaoluwa Ibiwoye (Discover Geoscience)
Abstract This study analysed the University of Ilorin Dam structurally using multi-criteria techniques to evaluate the dam’s functionality and prevent possible hazards associated with dam failure due to rock deformities. This objective was achieved through field geological mapping, remote sensing, and aeromagnetic techniques to determine the dam site’s structural trends. The geological data obtained was processed and plotted for the geologic map and rosette diagram of the structural trends. From this, it was noted that the geological structural trends within the site and the University campus are in the NE-SW direction. From the remote sensing map, it was observed that the dam is situated between major and minor fault lines trending in the NE- SW direction. From the aeromagnetic map, it was deduced that the magnetic susceptibility of the geologic materials around the dam site varies from low to medium magnetic strength, which has been interpreted as the materials being weathered. In addition, circular anomalies were noted on the aeromagnetic map, which could be a potential intrusion. The tilt derivative map suggests the dam is situated in an unstable geological area, which could lead to subsurface structural stress. The aeromagnetic lineament map agrees with remote sensing and reconnaissance survey structural trends. This means the subsurface evaluation agrees with surface observations. From the analysis, it is concluded that the dam’s structural integrity is compromised and the long-term stability of the dam is threatened, and this explains the inefficiency of the dam in serving the University community. Collaborative efforts are required between geologists, engineers, and other experts to mitigate the risks and ensure the dam’s stability.